THE PATHOGENETIC JUSTIFICATION OF METAL-ENZYMES HOMEOSTASIS IN COMMISSURE FORMATION DURING PERITONITIS - Клименко, Ю. А.; Клименко, А. О.; Попов, А. З.; Збирак, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The intraperitoneal commissure formation during peritonitis is connected with microbal invasion into abdominal cavity, that caused of peritoneum inflammation and exudates formation with acute conflict development between human immunity and bacterial aggression. The last one is presented by autoinfection with polymicrobal character (Streptococcus, Staphylococcus, Enterococcus, Candida, Pseudomonas aurogenosa) which needs the metal-enzymes for life and growth. The bacterial invasion into abdominal cavity caused to high quantities of immune complexes of toxins, which have of enzyme activity of microbal catalase, nuclease, hyaluronidase depended of metal content. We established of correlation between changes of quantities of microelements and metals: iron, cuprum, zink in exudates in abdomen and inflammation progression and commissure formation. It’s proven, that microelements like biotics activated of specific enzyme’ systems, which responsible for collagen synthesis which is basis of collagen structure and commissure formation. Suitable reaction for this agents is localization of inflammation process generalization and toxins dissemination in abdominal cavity by formation of commissures.